An Analysis of the Determining Factors of Mobile Banking Adoption in Islamic Banks. Issue 1 (July 2020) - Yussaivi, A; Suhartanto, D; Syarief, Moch. Edman
Abstract: This research is conducted to investigate the factors that influence the attitudes and perceptions of digital natives in using mobile banking and artificial intelligence (AI)-enabled mobile banking. Partial least squares were applied to examine the differential effects of technology-based (i.e. attitudes toward AI, relative advantage, trust, security in specific mobile banking activities), non-technology based (i.e. the need for service, quality of service) and religiosity. This study utilizes 339 digital native respondents. The questionnaire distributed to Islamic banking customers in three cities in Aceh Province, Indonesia. The study results the perceived trust construct, and the security in specific mobile banking activities is the major determinant of mobile banking adoption intention and also indicates a divide in how digital natives perceive the perceived trust between two dependent variables. Then the relative advantage construct has the most impact on mobile banking usage. However, the relative advantage was not significant for AI-enabled mobile banking. For managerial practices, this study provides guidelines for Islamic bank management to improve the trust, security and relative advantage of their mobile banking services as a strategy for developing the sustainability of the business.